Perancangan Sistem Informasi UMKM De’Sate Batam melalui Analisis Pengendalian Internal Menggunakan COSO Framework - Suwarno Suwarno; Verren Calystania; Veni Sisca; Jessica Novia; Vira Vira; Stephanie Stephanie (Prosiding, 2023)
With advances in technology in the current era, technology can make it easier for MSMEs to record more accurate financial reports so they can continue to survive and adapt to various conditions. The purpose of the research conducted was to analyze the state of MSME De'Sate through internal control using the COSO framework and then to design an information system through the UML Class Diagram and UI Layout Form modeling. The research approach was used by conducting direct observations and interviews with De'Sate MSME owners, with the types of data being primary data and secondary data obtained through literature studies. The research results obtained are as follows: (1) In maintaining the continuity of its business, De'Sate implements internal control with the COSO concept, (2) system design has been made using use case diagrams, UML class diagrams, and the creation of UI Layout forms and systems that made accompanied by a Point Of Sales (POS) so that De'Sate can improve the efficiency of the customer service process.